Redescription of the southernmost snake species, Bothrops ammodytoides (Serpentes: Viperidae: Crotalinae) - Carrasco, Paola (2010)
Bothrops ammodytoides is a pitviper species endemic to Argentina that inhabits arid and semiarid areas from sea level to more than 3000 m, reaching the southernmost latitude for snakes. According to previous studies, the species is placed in the Bothrops alternatus group. We redescribe Bothrops ammodytoides based on examination of 101 specimens and provide new data on lepidosis, hemipenial morphology, cranial osteology, variation in coloration, and distribution. We compare Bothrops ammodytoides with representative species of the genus and related genera. Morphological comparisons reveal considerable affinities between Bothrops ammodytoides, Bothrops pictus, Bothrops andianus, and Bothrocophias microphthalmus, suggesting that the current taxonomy for Bothrops ammodytoides requires to be reassessed.